Factors influencing students’ acceptance on online learning among UiTM Kampus Bandaraya Melaka students - Tumat, Nurul Amira (2020)
E-Learning or online learning is a new method to the academic intuitions where learning process requires the use of network environment called an Internet. During Movement Control Order (MCO) and it led to the closure of school and universities in Malaysia. So, many academic intuitions using online learning to ensure their academic activities work as usual and no need to extend their current semester. Acceptance on online learning is affected by the constraints of online learning features that are less interesting, less friendly and less attractive that result in students more comfortable connecting with lecturer and peers through other media platform such as Facebook and Email. There are several factors influencing students’ acceptance on online learning such as students’ attitude, instructors’ characteristics and interactive application. The purpose of this study is to examine the factors influencing students’ acceptance on online learning among UiTM Kampus Bandaraya Melaka. Total population for students of Human Resource Management in UiTM Kampus Bandaraya Melaka is 480 students. Hence, a sample size is 214 respondents to distributes questionnaire and the researcher used questionnaire as the method to collect data from the respondents. The data collected through the questionnaire are tested using the Statistical Packages for Social Sciences (SPSS) software. The findings of this study have shown that there is a relationship between students’ attitude and students’ acceptance on online learning and two variables which are instructors’ characteristics and interactive application shown that there is no relationship with students’ acceptance in online learning. Students’ attitude is most significant factor to the students’ acceptance, it shown increase students’ motivation and desires to complete their studies and can interact with technology.